USING VIDEO BLOGS AS AN EXTRACURRICULAR ACTIVITY FOR INTERNATIONAL STUDENTS AT THE INITIAL PHASE OF FOREIGN LANGUAGE LEARNING - Dragomyretska, Olga (PEOPLE: International Journal of Social Sciences, 2018)
The goal of the research consists in showing that application of a video blog as an extracurricular activity is a very effective interactive method that improves the process of the learning of a new language. The main research method was modeling the process of organizing extracurricular activity using a video blog for students at preparatory department of a non-language-centered university. A group of international students that was studying a foreign language created a video blog under the supervision of a teacher. The objective of this blog was preparation and uploading topical videos about different places in Odessa (Ukraine). Analyzing this project - the implementation of a video blog at the initial phase of foreign language learning – shows us that integration of topical video blogs into the learning process as an extracurricular activity enhances the students’ education in many ways: primarily, it cultivates communication skills, trains oral perception, improve understanding of native speakers and interest in a foreign language learning. We can conclude that the future development and implementation of blog-technology as an interactive method of extracurricular activity will be an important and useful tool.